High temperature dielectric studies of indium-substituted NiCuZn nanoferrites. (January 2018) - Hashim, Mohd.; Raghasudha, M.; Shah, Jyoti; Shirsath, Sagar E.; Ravinder, D.; Kumar, Shalendra; Meena, Sher Singh; Bhatt, Pramod; Alimuddin,; Kumar, Ravi; Kotnala, R.K.
Abstract: In this study, indium (In 3+ )-substituted NiCuZn nanostructured ceramic ferrites with a chemical composition of Ni0.5 Cu0.25 Zn0.25 Fe2-x Inx O4 (0.0 ≤ x ≤ 0.5) were prepared by chemical synthesis involving sol–gel chemistry. Single phased cubic spinel structure materials were prepared successfully according to X-ray diffraction and transmission electron microscopy analyses. The dielectric properties of the prepared ferrites were measured using an LCR HiTester at temperatures ranging from room temperature to 300 °C at different frequencies from 10 2 Hz to 5 × 10 6 Hz. The variations in the dielectric parameters ε ′ and ( tanδ ) with temperature demonstrated the frequency- and temperature-dependent characteristics due to electron hopping between the ions. The materials had low dielectric loss values in the high frequency range at all temperatures, which makes them suitable for high frequency microwave applications. A qualitative explanation is provided for the dependences of the dielectric constant and dielectric loss tangent on the frequency, temperature, and composition. Mӧssbauer spectroscopy was employed at room temperature to characterize the magnetic behavior. Highlights: Particles size of Ni0.5 Cu0.25 Zn0.25 Fe2-x Inx O4 (0.0 ≤ x ≤ 0.5) measured 25–34 nm. Low dielectric loss in the high frequency range at all temperatures. In 3+ -substituted nanoferrites suitable for high frequency microwave applications. Mössbauer spectra demonstrated their magnetically ordered behavior.